2018
DOI: 10.1093/sysbio/syy020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gene Flow on Coalescent-based Species-Tree Inference

Abstract: Most current methods for inferring species-level phylogenies under the coalescent model assume that no gene flow occurs following speciation. Several studies have examined the impact of gene flow (e.g., Eckert and Carstens 2008; Chung and Ané 2011; Leaché et al. 2014; Solís-Lemus et al. 2016) and of ancestral population structure (DeGeorgio and Rosenberg 2016) on the performance of species-level phylogenetic inference, and analytic results have been proven for network models of gene flow (e.g., Solís-Lemus et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 29 publications
5
107
0
Order By: Relevance
“…The varying placements of the Orbiculate clade when analyzing different datasets and/or using different approaches to estimate the species tree seems to be primarily the product of the inconsistency of species tree estimation in the presence of gene flow (Solís‐Lemus et al ., ; Long & Kubatko, ). Our network analysis of the HYBRID‐REDUCED dataset using P hylo N et revealed that all models involving reticulation events fit our data better than any model with strict bifurcating trees (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The varying placements of the Orbiculate clade when analyzing different datasets and/or using different approaches to estimate the species tree seems to be primarily the product of the inconsistency of species tree estimation in the presence of gene flow (Solís‐Lemus et al ., ; Long & Kubatko, ). Our network analysis of the HYBRID‐REDUCED dataset using P hylo N et revealed that all models involving reticulation events fit our data better than any model with strict bifurcating trees (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when investigating the evolutionary history of species, typically, strictly bifurcating species tree methods that account only for ILS are applied, and the potential impact of gene flow is not taken in account during the inference process. Moreover, mounting evidence that species tree methods are inconsistent in the presence of gene flow (Solís‐Lemus et al ., ; Long & Kubatko, ) demonstrates the need to incorporate methods that account for ILS and gene flow simultaneously in phylogenetic studies. Here, we present a clear example of the utility of these methods to clarify the evolutionary history of Lachemilla .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) calculated gene-tree probabilities under an introgression model, arguing that the concept of a species tree is poorly defined when there is gene flow. Long and Kubatko (2018) studied the probabilities of gene tree topologies under an isolation-with-initial-migration model (Wilkinson-Herbots, 2012) for three species, in which there is initial gene flow between sister species after their divergence. One might expect gene flow between sister species to make them appear more similar, making it easier to infer the species tree, but surprisingly with different population sizes, gene flow between sister species can cause the most probable gene tree topology to differ from the species tree, leading to so-called anomalous gene trees.…”
mentioning
confidence: 99%
“…Therefore, SVDquartets allows the consideration of both mutational and coalescent variance in the estimation of phylogenetic relationships (Chifman & Kubatko, 2014). SVDquartets has also been shown to perform better than other species tree inference programs in presence of gene flow (Long & Kubatko, 2018). SVDquartets assumes that each site has its own genealogy drawn from the coalescent model (Chifman & Kubatko, 2014).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%